PENDAMPINGAN PEKERJA SOSIAL DALAM REHABILITASI SOSIAL ORANG DENGAN HIV AIDS (ODHA) IN SOCIAL WORKING ASSISTANCESOCIAL REHABILITATION OF PEOPLE LIVING WITH HIV AIDS (PLWHA) - tursilarini, Tateki Yoga; Hermawati, Istiana; Hermawati, Istiana (Jurnal Penelitian Kesejahteraan Sosial, 2019)
abstract HIV-infected individuals, mostly showing changes in their psychosocial character such as living in stress, depression, feeling lack of social support. It takes someone who can accept the condition of PLWHA, for example medical personnel, social workers, social volunteers or institutions / institutions that care about PLWHA. PLWHA need social rehabilitation to restore and strengthen so that they can grow confidence in facing their suffering. This study aims to describe the qualifications of social workers; Describe the services of social workers in the social rehabilitation of PLWHA. Data sources are social workers, beneficiaries of PLHIV, social rehabilitation departments. Technique of collecting interview and observation data, qualitative descriptive data analysis.The research findings were educational qualifications for social workers at the Wasana Bahagia Ternate PLHIV Rehabsos Hall for six people who were majoring in Social Welfare, three non-Social Welfare people, and one high school social work. Social Workers have the duty and function to assist PLWHA from the initial process (assessment) to the end (termination). Social workers carry out networking; assessment; medication compliance; psychosocial assistance; mentoring social rehabilitation intervention processes: re-preparing families and communities. Recommendations, 1) Social Workers need to increase and add insight into knowledge about PLWHA; 2) Need to improve the mentoring techniques for PLWHA because knowledge develops very quickly; 3) Community education activities continue to be proclaimed about a healthy lifestyle and anti-discrimination against PLWHA awareness for the community about the dangers of contracting the HIVAIDS virus. At the lowest level at the RT / RW level, families, schools, communities, religious leaders need 2) Family alignments and the community towards PLWHA, so that they do not feel alone in living their future. Keywords: Mentoring, Social Workers, Social Rehabilitation, PLWHA abstrak Individu yang terinfeksi HIV, sebagianbesar menunjukkan perubahan dalam karakter psikososialnya seperti hidup dalam stres, depresi,merasa kurang adanya dukungan sosial. Dibutuhkan seseorang yang dapat menerima kondisi ODHA, misalnya tenaga medis, pekerja sosial, relawan sosial ataupun lembaga/institusi yang peduli terhadap ODHA.ODHA membutuhkan rehabilitasi sosial untuk memulihkan dan memperkuat agar mereka dapat tumbuh kepercayaan diri dalam menghadapi penderitaannya. Penelitian ini bertujuan mendeskripsikan kualifikasi pekerja sosial dan mendeskripsikan pelayanan pekerja sosial dalam rehabilitasi sosial ODHA.Sumber data adalah pekerja sosial, penerima manfaat ODHA, dan Kabid Rehabilitasi Sosial. Teknik pengumpulan data wawancara dan observasi, analisis data deskriptif kualitatif. Temuan penelitian adalah kualifikasi pendidikan pekerja sosial di Balai Rehabsos ODHA Wasana Bahagia Ternate enam orang pendidikan jurusan Kesejahteraan Sosial, tiga orang non Kesejahteraan Sosial, dan satu orang Sekolah Menengah Atas Pekerjaan Sosial. Pekerja Sosial memiliki tugas dan fungsi untuk melakukan pendampingan ODHA dari proses awal (assesmen) sampai akhir (terminasi). Pekerja sosial melaksanakan jejaring kerja; assesmen; kepatuhan minum obat; pendampingan psikososial; pendampingan proses intervensi rehabilitasi sosial: penyiapan kembali keluarga dan masyarakat.Rekomendasi, 1) Bagi Pekerja Sosial perlu peningkatan serta tambahan wawasan pengetahuan tentang ODHA; 2) Perlu peningkatan tentang teknik-teknik pendampingan terhadap ODHA karena pengetahuan berkembang dengan sangat cepat; dan 3) Kegiatan edukasi kepada masyarakat terus dicanangkan tentang pola hidup sehat dan anti diskriminasi terhadap ODHA penyadaran bagi masyarakat akan bahaya terjangkit virus HIVAIDS. Sampai di level paling bawah tingkat RT/RW, keluarga, sekolah, masyarakat, tokoh agama perlu 4) Keberpihakan keluarga dan masyarakat terhadap ODHA, agar mereka tidak merasa sendirian menjalani masa depannya. Kata kunci: Pendampingan, Pekerja Sosial, Rehabilitasi Sosial, ODHA Â